Characteristics of the Status Identity and Consumption of the Middle Class. Issue 6 (1st November 2016) - Tikhonova, N.E.
Abstract : The article examines the dynamic of the middle class based on materials of nationwide surveys conducted by the Institute of Sociology, Russian Academy of Sciences. It finds that Russian society has become a society of a mass lower-middle class. It offers an assessment of the possibilities and necessary conditions for the expansion of the middle class in Russia. It finds that the numerical dominance of positions that are peripheral to it in the composition of the middle class is conditioned by the model of the Russian economy, in which the percentage of positions of professionals, managers, and entrepreneurs is relatively low. It demonstrates that the Russian middle class is characterized by specific stratal identities, making it possible to speak of the beginnings of the formation of a class consciousness in it. It cites characteristics of the lifestyle and consumption of the middle class. It finds that while retaining a significant separateness from other Russians in the period from 2003, members of the middle class were characterized by a worse dynamic of indicators in Russia. The nucleus of the middle class were in the least well-off position.